2000
DOI: 10.1149/1.1394008
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Ballmilled Pt-Mo Catalysts for Polymer Electrolyte Fuel Cells and Their Tolerance to CO

Abstract: Polymer electrolyte fuel cells are clean, efficient electrical generators based on the electrochemical oxidation of hydrogen by oxygen. Both electrochemical reactions require catalysts such as Pt to operate at a useful rate. However, Pt is easily poisoned by CO, and significant power losses may arise when H 2 is obtained from the reforming of alcohols or hydrocarbons. Even 10 ppm CO in the H 2 feedstream has a detrimental effect on the fuel cell performance. 1 Binary electrocatalysts have been used with succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The existence of surface PtO x has already been demonstrated in numerous studies , that showed that, in ultrahigh vacuum, molecular oxygen dissociates and chemisorbs onto Pt, even at cryogenic temperatures. In particular, Gouérec et al have shown, by in situ reduction in fuel cells, that oxidized Pt occurs exclusively at the nanoparticle surface. There are no reports of the true O:Pt atomic ratios.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of surface PtO x has already been demonstrated in numerous studies , that showed that, in ultrahigh vacuum, molecular oxygen dissociates and chemisorbs onto Pt, even at cryogenic temperatures. In particular, Gouérec et al have shown, by in situ reduction in fuel cells, that oxidized Pt occurs exclusively at the nanoparticle surface. There are no reports of the true O:Pt atomic ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Probable solution to overcome the poisoning effects in fuel cell is to use alloyed catalysts, such as Pt/Ru, Pt/Mo, Pt/Ru/Mo, Pt/Sn, Pt/Ru/WO 3 , etc. 22–25. A carbon‐supported Pd‐based PdPt catalyst with a Pd:Pt atomic ratio of 19:1 was synthesized and applied to a polymer electrolyte membrane fuel cell.…”
Section: Introductionmentioning
confidence: 99%
“…Since the mid-1990s, we have been developing the high energy ball-milling technique combined with a leaching procedure to produce unsupported Pt-based catalysts [28][29][30]. The high energy ball-milling technique, also called mechanical alloying, is a solid-state method for the synthesis of metallic powders or ceramics.…”
Section: Introductionmentioning
confidence: 99%